Penggunaan Google Classroom Bagi Guru Sekolah Dasar Negeri 170 Palembang Sebagai Platform Pembelajaran Daring di Masa Pandemi Covid-19 - Guntoro Barovih; Muhammad RidhoArdiansyah; Deli Abdurunnapis Hutanegara (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Indonesia is currently facing the Covid-19 pandemic situation, where we are entering the New Normal stage. This New Normal stage changes the process of educational activities, conventional education is changed to New Normal era education. New Normal era education in the implementation of learning involves the use of technology, technology in delivering material to students in their respective educational units. The Ministry of Education and Culture of Indonesia officially conveys on the official website kemdikbud.go.id about Guidelines for the Implementation of Learning in the Academic Year and the New Academic Year in the New Normal Period. yellow, orange, and red zones are prohibited from conducting face-to-face learning in education units. Education units in these zones continue to learn by learning from home. This community service for SD Negeri 170 Palembang teachers aims to introduce the Google Classroom application as a means of supporting learning activities. The method in this service activity is training. The results obtained from this training activity on the use of Google Classroom are that it can increase teachers' understanding of technology that can be utilized optimally in conducting teaching and learning activities.